Characteristics of Learning Assessment Towards Implementation of Merdeka Learning Curriculum (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Assessment is essential to the curriculum to measure and assess competency levels. The implementation of the independent learning curriculum assessment is directed at sustainable assessments. A meaningful learning process requires a good, planned, and irrational assessment system. The research aims to describe the characteristics of the assessment in the implementation of the independent curriculum, including the knowledge of the school community, the process of planning, implementation, processing of assessment results, reporting on learning progress and obstacles along with school and teacher solutions in carrying out assessments in the independent curriculum. This research is qualitative descriptive. The study was conducted in June-December 2022 at SMP Muhammadiyah 02 Batu. The research population was all teachers at SMP Muhammadiyah 02 Batu. The research sample was all SMP Muhammadiyah 02 Batu teachers using a saturated sampling technique. The instruments used are interview guidelines, observations, and documentation. Data analysis was carried out descriptively. The results showed that the teacher understood the independent learning curriculum well. Schools began to apply learning and assessment principles, planning lessons and assessments, understanding learning outcomes, planning learning and assessments, implementing learning and assessments, and processing and reporting assessment results. Teachers generally carry out summative and formative assessments, while minimal diagnostic assessments are carried out. Regardless of the results of the research, future researchers can make efforts to assist teachers in overcoming obstacles to implementing assessments in the independent curriculum.